Hypernasal Speech Is Perceived as More Monotonous than Typical Speech - Tardif, Monique; Berti, Larissa Cristina [UNESP]; Castro Marino, Viviane Cristina de [UNESP]; Pardo, Jennifer; Bressmann, Tim (Karger, 2018)
Background/Purpose: Anecdotal clinical reports have stated that hypernasal speech sounds monotonous. However, the relationship between the perception of intonation (i.e., the fundamental frequency variation across an utterance) and hypernasality (excessive nasal resonance during the production of non-nasal sounds) has not been investigated in research. We hypothesized that auditory-perceptual ratings of intonation would be significantly lower for more hypernasal stimuli. Methods: One male and one female voice actor simulated 3 levels of intonation (monotone, normal, and exaggerated) at 4 different levels of hypernasality (normal, mild, moderate, and severe). Thirty participants listened to the simulations and rated the intonation on a visual analogue scale from 0 (monotone) to 100 (exaggerated). Results: A mixed-effects ANOVA revealed main effects of intonation (F-2 = 236.46, p < 0.001), and hypernasality (F-3 = 159.89, p < 0.001), as well as an interaction between the two (F-6 = 28.35, p < 0.001). Post hoc analyses found that speech was rated as more monotonous as hypernasality increased. Summary/Implications: The presence of hypernasality in speech can lead listeners to perceive speech as more monotonous. Instrumental measures should be used to corroborate auditory-perceptual evaluations of speech features like intonation. (c) 2018 S. Karger AG, Basel
Keywords: Hypernasality; Intonation; Perception of speech; Ratings of speech; Instrumental measures; Auditory-perceptual evaluations